PENGEMBANGAN E-MODUL BERBASIS MODEL KOOPERATIF TIPE STAD PADA MATERI SISTEM PENCERNAAN DI KELAS XI SMA - Dwi Mayasari; Suwondo Suwondo; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aims to develop an e-module based on the STAD (Student Teams Achievement Division) cooperative model for the topic of the digestive system in class XI Senior High School, in terms of validity and practicality. The development of the e-module uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted until the Development stage and carried out from December 2021 to March 2023. The instruments used in this research were validation sheets and response questionnaires to determine the level of validity and practicality of the product. The results of the validation stage in terms of content, language, presentation, and usage aspects showed a score of 97.4%, indicating with very valid category. The results of the limited trial showed a score of 92.0% with very practical category. Based on the average scores of validity and practicality, the e-module obtained a score of 94.7% with very feasible category. Based on these findings, the developed e-module is considered suitable for use as a supporting teaching material for learning the digestive system topic in class XI Senior High School.Key Words: Teaching Materials; E-Module; Digestive System; STAD.